The influence of social media marketing on online consumer behavior - Zhigui Jimenez, Joseline del Carmen; Lima Azanza , Karla Elizabeth; Muñoz Suarez , Manuel Antonio (mktDESCUBRE; Vol 1 No 21 (2023): Twenty-first Edition (January - June), 2023)
The objective of this article is to determine how Social Media Marketing has influenced the behavior of post Covid-19 consumers. For this, the company Massuh, an important distributor based in the city of Guayaquil, has been taken as a reference. Theoretical constructs related to digital marketing and social networks were analyzed in order to obtain a better understanding of the object of study. The methodology had a mixed approach (quantitative and qualitative) since surveys were used to collect information from consumers and collaborators of the Massuh company and an interview model for the general manager was also applied. The expected results are aimed at knowing the level of influence that social media marketing has on the behavior of post Covid-19 consumers and, as a result, establishing the respective conclusions.